AN ANALYSIS OF SIMILE FIGURES OF SPEECH IN KATY PERRY’S SONG “FIREWORK” - Butar-Butar, Silvia; Nasution, Jamaluddin; Arnelita, Tia; Manullang, Riyanti Agni Hotthere; Hutauruk, Gracia Anggelika (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: This study examines the employment of simile in Katy Perry's song "Firework" and its contribution to expressing themes of motivation and self-empowerment. This study emphasizes the significance of figures of speech as a stylistic device that enhances and reinforces meaning in literary works, including popular song lyrics. This study aims to identify similes included in the song, to comprehend the significance of these similes, and to investigate the moral and inspiring themes embedded in the song lyrics. The methodology employed is qualitative research utilizing a descriptive technique, wherein data is gathered through a comprehensive textual study of the lyrics of "Firework." Observation and note-taking procedures were used for data collection to identify and interpret the similes. The study's results demonstrate that similes successfully convey emotions of fragility and doubt alongside the resilience to rise and exhibit confidence. The employment of similes facilitates the creation of distinct visual imagery and elicits profound emotional responses, rendering the song's motivational and inspiring lyrics more vivid and accessible to the audience. Similes strengthen language and provide artistic worth and significance to songs. According to this study, similes are important expressive instruments in popular music, sending encouraging messages of courage and hope to listeners. Keyword: figures of speech;simile;firework;katy perry;song lyrics. Abstrak: Penelitian ini mengkaji penggunaan majas simile dalam lagu Katy Perry “Firework” dan kontribusinya dalam mengekspresikan tema motivasi dan pemberdayaan diri. Penelitian ini menekankan pentingnya majas untuk memperkaya dan memperkuat makna dalam karya sastra, termasuk lirik lagu populer. Penelitian ini bertujuan untuk mengidentifikasi majas simile yang terdapat dalam lagu, memahami makna majas tersebut, serta menganalisis tema moral dan inspiratif yang tertanam dalam lirik lagu. Metodologi yang digunakan adalah penelitian kualitatif dengan teknik deskriptif, di mana data dikumpulkan melalui studi teks komprehensif terhadap lirik “Firework.” Prosedur pengamatan dan pencatatan digunakan untuk pengumpulan data guna mengidentifikasi dan menafsirkan majas simile. Hasil penelitian menunjukkan bahwa majas simile berhasil menyampaikan emosi kerentanan dan keraguan bersamaan dengan ketahanan untuk bangkit dan menunjukkan kepercayaan diri. Penggunaan simile memfasilitasi pembentukan gambaran visual yang unik dan memicu respons emosional yang mendalam, sehingga lirik lagu yang motivasional dan menginspirasi menjadi lebih hidup dan mudah dipahami oleh pendengar. Majas simile memperkuat bahasa dan memberikan nilai artistik serta makna pada lagu. Menurut penelitian ini, majas simile merupakan alat ekspresif yang penting dalam musik populer, menyampaikan pesan-pesan penyemangat tentang keberanian dan harapan kepada pendengar. Kata kunci: majas;simile;firework;katy perry;lirik lagu.